2007
DOI: 10.1186/1471-2180-7-102
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanisms of Legionella pneumophila-induced interleukin-8 expression in human lung epithelial cells

Abstract: Background: Legionella pneumophila is a facultative intracellular bacterium, capable of replicating within the phagosomes of macrophages and monocytes, but little is known about its interaction with human lung epithelial cells. We investigated the effect of L. pneumophila on the expression of interleukin-8 (IL-8) in human A549 alveolar and NCI-H292 tracheal epithelial cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…Nevertheless, the results regarding TSA and anacardic acid effects on IL-8 expression were qualitatively comparable. Teruya et al (25) found similar IL-8 levels after infecting A549 or NCI-H292 cells. Therefore, observed IL-8 levels are comparable to other in vitro studies of primary lung epithelial cells and cell lines.…”
Section: Discussionmentioning
confidence: 66%
“…Nevertheless, the results regarding TSA and anacardic acid effects on IL-8 expression were qualitatively comparable. Teruya et al (25) found similar IL-8 levels after infecting A549 or NCI-H292 cells. Therefore, observed IL-8 levels are comparable to other in vitro studies of primary lung epithelial cells and cell lines.…”
Section: Discussionmentioning
confidence: 66%
“…The capacity of Hsp90 inhibitors to blunt IL-8 production was recently reported in the context of bacterial-and viralinduced inflammation, including Helicobacter pylori-infected gastric epithelial cells (Yeo et al 2004), Legionella pneumophila-infected lung epithelial cells (Teruya et al 2007), Bacteroides fragilis enterotoxin-treated intestinal epithelial cells (Kim et al 2009), and oncogenic herpes virusinfected endothelial cells and fibroblasts (Defee et al 2011). In these experimental studies, Hsp90 inhibitors acted via deactivation of NFκB, a client of Hsp90 and one of the major transcription factors for IL-8 (Hoffmann et al 2002;Salminen et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Cianciotto; Northwestern University Medical School, Chicago, USA [31]), strain JR32 (wild type), JR32 DdotA deficient in dot/icm, encoding a protein essential for the type IVB secretion system (kindly provided by H. Shuman; Dept of Microbiology, Columbia University Medical Center, New York, NY, USA), strain Corby (wild-type), Corby DflaA deficient in flagellin (kindly provided by K. Heuner; Robert Koch-Institut, Berlin, Germany), as well as type II secretion system knockout Corby DlspDE [7,32] (also kindly provided by K. Heuner), were routinely grown on buffered charcoalyeast extract agar for 2-3 days at 37uC before use [33]. A549 cells were infected with L. pneumophila with a multiplicity of infection (MOI) of 10 at 37uC and 5% CO 2 .…”
Section: Cell Linesmentioning
confidence: 99%
“…Although L. pneumophila efficiently infects and stimulates lung epithelial cells [4][5][6][7] and GM-CSF has been shown as important for bacteria elimination via phagocytosis, mechanisms of L. pneumophila-induced release of this cytokine are widely unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation